Analisis Kesulitan Siswa dalam Menerjemahkan Teks pada Mahasiswa Program Studi Bahasa Inggris di UMNU Kebumen - Hanivah, Nurul; Andika, Alek (English Education and Literature Journal (E-Jou), 2023)
English Plays Important Role To Communicate In This Globalization Era. Unfortunately, Our Young Generation Still Need Many Improvements In English Mastering. One Of The Biggest Problems Is Because They Cannot Understand The Language. Therefore, This Research Aimed To Identified The Students’ Difficulties In Translating Text Both From English To Indonesian Or The Contrary. This Research Applied Qualitative Approach With Descriptive Method. The Sample Was Taken By Using Purposive Sampling Technique And It Was Decided That There Were Eleven (11) Students Who Fulfilled The Criteria. The Researcher Used Three (3) Kind Of Instruments; Objective Test, Questionnaire, And Interview. From The Identification Result, The Researcher Found That There Were Three (3) Dominant Difficulties Encountered By The Students; (1) Idioms, (2) Unsystematic Mind Plot, And (3) Equivalent Word. Furthermore, The Researcher Concluded That To Overcome Those Difficulties, The Students Should; Do More Reading Activity, Increase Knowledge And Literacy, Learn Grammar, Learn Theory Of Translation, And Do More Practice.  Keyword: Analysis, Difficulty, Translating